Application of Dijkstra’s Algorithm in Searching the Shortest Path of Coal Production Locations - Amelia Yusnita; Siti Lailiyah; I Gede Adi Merta (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
To exploit coal the company needs to hold discussions and it takes time to reach the location, each coordinate point traveled has a different distance, the shorter the distance, the faster the time it will take. In this problem the company does not yet have hauling distance data at each coordinate point, the solution to this problem is how to build an application for determining coal production points using the dijkstra algorithm. There are three stages used to collect data, namely, literature study, observation, and interviews. The development of the system used to build this application uses the prototype method whose stages consist of communication, rapid planning, rapid design modeling using flowcharts, prototype formation, and submission of the customer system in the form of an application that analyzes the determination of PIT location distances using algorithms dijkstra, the output of this application is a description of the track map display, the destination location and its node points with detailed routes with a distance of kilometers. At this stage, the application is tested using the blackbox test, by checking whether the buttons can function properly and the expected result from this test is a success.